Coach characteristics and their impact on substitution decisions - Lars Vischer (Universität Münster, Institut für Organisationsökonomik, 2024)
This study analyses the factors influencing coaching decisions when substituting players, particularly in light of the rule change from three to five permitted substitutions. To this end, 161 coaches and their decisions are analysed in 1,836 Bundesliga matches from 2017/2018 to 2022/2023, whereby the tactical components, timing and age structure of the substitutions are examined. A total of 13,363 substitution situations are therefore analysed at the level of individual decisions. The main influencing factors are the age of the coach, professional experience and the length of time spent working with the team. Spectator numbers and goal difference hardly play a role. – – Diese Studie untersucht die Einflussfaktoren auf Trainerentscheidungen bei Spielerwechseln, insbesondere vor dem Hintergrund der Regeländerung von drei auf fünf erlaubte Wechsel. Dazu werden 161 Trainer und deren Entscheidungen in 1.836 Bundesligaspielen von 2017/2018 bis 2022/2023 analysiert, wobei die taktische Komponente, der Zeitpunkt und die Altersstruktur der Wechsel untersucht werden. Insgesamt werden somit 13.363 Wechselsituationen auf Ebene der individuellen Entscheidungen betrachtet. Wesentliche Einflussfaktoren sind das Alter des Trainers, die Berufserfahrung und die Dauer der Zusammenarbeit mit der Mannschaft. Zuschauerzahlen und Tordifferenz spielen hingegen kaum eine Rolle.
Keywords: D81; D91; L83; M50; Z20; Z21; 650; Coach; Decision; Leadership; Rule Change; Substitution